Adubação de sistemas: antecipação de adubação nitrogenada para a cultura do milho em integração lavoura-pecuária - Bortolli, Marcos Antonio de (2016)
Traditionally in no-tillage systems, fertilization is done to the catch crop. In general nutrient cycling in crop systems has not been treated as an important tool in the process of nutrient supplying for plants. The type and the condition in which vegetable residuesis decomposed can affect the efficiency of nutrient cycling.This study assessed the effect of anticipated nitrogen fertilization in crop-livestock systems on cultivated cornproduction, rate ofnutrient release from plant residue, and theN-minerallevels of soil. The study was carried out in the city Abelardo Luz (SC) in a Clayey Oxisol. The experimental design was a randomized block design with three replications. The treatments were arranged in a 2 x 2 factorial arrangement. The first factor was N Fertilization Time: in the N-Pasture level, nitrogen (200 kg ha-1 N) and N-Grains level, no nitrogen was applied. The second factor was the Grazing Height, characterized by two sward heights of oat at 15 cm (Low Height Pasture) and at 30 cm (High Height Pasture). Corn hybrid ‘Máximus’ was sowed in 10thOctober, 31 days after the removal of animals. In the twelve resulting plots from the combination of treatments on pasture phase (N Fertilization Time x Grazing Height) rates of N-fertilizer (0, 100, 200 e 300 Kg ha-1 of N) as urea were allocated in the split plot.We conclude that anticipated N fertilization of winter cover crop pasture to provide high-quality forage and carry-over N to the subsequent corn crop and may eventually replace side drees nitrogen fertilization on corn and can improve overall N fertilizer efficiency use in integrated crop-livestock systems.The rate of K release from plant residues is very fast, releasing large quantities in the first days after plant desiccation.Despite of considerably high nitrogen dose used in both the pasture and at the grain crop it was not observed nitrate leaching risks during the study period.